3 - Rites et Condition Humaine : Leçon sur les leçons des pères - Lamine Ndiaye (African Sociological Review, 2013)
Rite is a fundamental human activity. Therefore, we can, suggest that “our” social life exists and has meaning only because of ritual activities. Thus, through the rites of initiation and death, human beings seek to establish peace, both mental somatic and social, that they need to survive. in the context of African communities, we argue that rituals are not a matter of fun but the foundation upon which life is built.